Interleukin-2 is required for NKp30-dependent NK cell cytotoxicity by preferentially regulating NKp30 expression - Kim, Nayoung; Yi, Eunbi; Lee, Eunbi; Park, Hyo Jin; Kim, Hun Sik (Frontiers in Immunology, 2024)
Natural killer (NK) cells are key effectors in cancer immunosurveillance, eliminating a broad spectrum of cancer cells without major histocompatibility complex (MHC) specificity and graft-versus-host diseases (GvHD) risk. The use of allogeneic NK cell therapies from healthy donors has demonstrated favorable clinical efficacies in treating diverse cancers, particularly hematologic malignancies, but it requires cytokines such as IL-2 to primarily support NK cell persistence and expansion. However, the role of IL-2 in the regulation of activating receptors and the function of NK cells expanded for clinical trials is poorly understood and needs clarification for the full engagement of NK cells in cancer immunotherapy. Here, we demonstrated that IL-2 deprivation significantly impaired the cytotoxicity of primary expanded NK cells by preferentially downregulating NKp30 but not NKp46 despite their common adaptor requirement for expression and function. Using NK92 and IL-2-producing NK92MI cells, we observed that NKp30-mediated cytotoxicity against myeloid leukemia cells such as K562 and THP-1 cells expressing B7-H6, a ligand for NKp30, was severely impaired by IL-2 deprivation. Furthermore, IL-2 deficiency-mediated NK cell dysfunction was overcome by the ectopic overexpression of an immunostimulatory NKp30 isoform such as NKp30a or NKp30b. In particular, NKp30a overexpression in NK92 cells improved the clearance of THP-1 cells in vivo without IL-2 supplementation. Collectively, our results highlight the distinct role of IL-2 in the regulation of NKp30 compared to that of NKp46 and suggest NKp30 upregulation, as shown here by ectopic overexpression, as a viable modality to harness NK cells in cancer immunotherapy, possibly in combination with IL-2 immunocytokines.